Comparaison de la composition corporelle obtenue par bio-impédance et par absorptiométrie biphotonique chez des sportifs de haut niveau - Pineau, J. C.; Frey, A. (Science & Sports, 2014)
Introduction: The purpose of this study was to compare fat-free mass between bioelectrical impedance analysis and dual-energy X-ray absorptiometry DXA and total body water measured by BIA and estimated from the fat-free mass DXA. Synthesis of the facts and results: Thirty athletes, practising various sports in weighty categories, were simultaneously examined by both techniques of BIA and DXA. We found significant differences of fat-free mass between these two techniques. In the majority of the cases, total body water measured by bio-impedance and estimated by fat-free mass DXA presents gaps superior to ± 2%. Conclusion: Bioelectrical impedance technique and absorptiometry DXA should not be used interchangeably.